The worth of Javanese conservative leadership in coping with COVID-19 - Wawan Sobari (Masyarakat, Kebudayaan dan Politik, 2022)
Current studies discover the difference of response of conservatism to the COVID-19 pandemic situation with, at least, six stigmas, namely practicing conservative politics, high risk public health behavior, lack of trust in science, neglecting mainstream media reports, less support for vaccination, and tendency to stockpile. This fieldwork-based qualitative study aims to explore the conservative political leadership of a village head in dealing with the pandemic situation. Unlike the previous studies, it reveals the village head’s conservative leadership which plays a vital role in coping with the outbreak. Under the influence of Javanese culture and tradition, the practices of leadership have positive impacts on controlling the situation, that are responsiveness, willingness to hear input, empathy, direct engagement, non-discrimination, ability to mobilize village apparatuses and to encourage participation of villagers, and consistent reminders to villagers to adhere to health protocols. The village head operationally practices the values of ngancani (accompanying) and njagongi (hanging out) in his leadership. The findings challenge previous academic works as the leadership adjusts to dominant Javanese conservatism in handling the pandemic. It negates the view of difference of conservatism’s response to the outbreak. Conservatism, particularly Javanese cultural and traditional values, actually minimizes the differences of social identity among villagers.